Legitimate kid : a memoir - Rodriguez, Aida (HarperOne, an imprint of HarperCollins Publishers, 2023)
"A poignant and moving memoir-in-essays from stand-up comedian Aida Rodriguez on the power of overcoming hardship and transforming pain into laughter"--